Determinants and group differences in international undergraduates’ engagement in Chinese higher education - Jun Qu; Dharm Dev Bhatta (PLoS ONE, 2025)
Student engagement is a crucial indicator of academic success, quality education, and overall development, encompassing behavioral, cognitive, and emotional dimensions. This study aimed to investigate the levels and key determinants of engagement among international undergraduate students in China, to gain a deeper understanding of the individual and contextual factors that shape their learning experiences. Data were collected from 721 international students enrolled in 21 non-double-first-class universities in Yunnan and Guangxi provinces, using a structured questionnaire adapted from the National Survey of Student Engagement-China, the China College Student Survey, and the Motivated Strategies for Learning Questionnaire. The results revealed a moderate level of overall engagement (M = 4.02 on a 5-point scale), with emotional engagement scoring the highest (M = 4.10), followed by behavioral (M = 3.99) and cognitive engagement (M = 3.98). A gender-based analysis revealed significant differences in cognitive performance (p < 0.01, Cohen’s d = 0.27) and overall engagement (p < 0.05, Cohen’s d = 0.17), with males scoring higher. Academic discipline and grade level were also significantly associated with engagement dimensions, while Chinese language proficiency showed no significant effect. Regression and Structural Equation Modeling(SEM) analyses identified cultural adaptation (β = 0.35), self-efficacy (β = 0.34), teacher behavioral support (β = 0.29), and peer behavioral support (β = 0.25) as strong and significant predictors, collectively explaining over 60% of the variance in students’ overall engagement(χ²/df = 2.12, CFI = 0.98, TLI = 0.97, RMSEA = 0.04, and SRMR = 0.03). The findings suggest that institutions must strengthen culturally responsive pedagogies, enhance support structures, and promote active learning strategies to improve international students’ engagement and academic success in Chinese higher education.